2022
DOI: 10.5937/medi55-40195
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative anxiety: An important, but neglected issue

Abstract: Preoperative anxiety refers to a state of discomfort caused by an upcoming operation, anesthesia, the disease itself, or hospitalization. Although the reported incidence of preoperative anxiety varies in a wide range, the majority of surgical patients experience at least some degree of anxiety preoperatively and it can be frequently seen in the preoperative setting. The specific factor that contributes most to the emergence of perioperative anxiety has not been identified yet. Still, older age and female gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 58 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Subjective scales are the most commonly used method for assessing preoperative anxiety. Several reliable scales are available, such as the Hospital Anxiety and Depression scale (HADS) [38], Visual Analogue Scale for Anxiety (VAS-A) [39,40], State-Trait Anxiety Inventory (STAI) [41], Amsterdam Preoperative Anxiety and Information Scale (APAIS) [42], Linear Analog Anxiety Scale (LAAS), and Multiple Affect Adjective Check List (MAACL) [43]. The VAS-A is the simplest to use, consisting of a 100 mm horizontal line, marked with zero at its left end and 100 at its right end.…”
Section: Measurement Of Preoperative Anxietymentioning
confidence: 99%
See 2 more Smart Citations
“…Subjective scales are the most commonly used method for assessing preoperative anxiety. Several reliable scales are available, such as the Hospital Anxiety and Depression scale (HADS) [38], Visual Analogue Scale for Anxiety (VAS-A) [39,40], State-Trait Anxiety Inventory (STAI) [41], Amsterdam Preoperative Anxiety and Information Scale (APAIS) [42], Linear Analog Anxiety Scale (LAAS), and Multiple Affect Adjective Check List (MAACL) [43]. The VAS-A is the simplest to use, consisting of a 100 mm horizontal line, marked with zero at its left end and 100 at its right end.…”
Section: Measurement Of Preoperative Anxietymentioning
confidence: 99%
“…While numerous studies have demonstrated its effectiveness [38][39][40], questions persist regarding the optimal methods for delivering patient education. Some experts advocate for the use of phone, written materials, or video resources [41,42], while other research suggests that direct personal interaction and verbal communication significantly alleviate anxiety symptoms [43,44]. Additionally, modern technologies, including mobile applications [46], online resources [47], and even virtual reality tools [48], have proven effective in managing anxious patients.…”
Section: Management Of Preoperative Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…While age and female gender have consistently emerged as distinct predictors of preoperative anxiety in numerous research investigations [29][30][31], a singular, definitive factor contributing to preoperative anxiety remains elusive. Further research endeavors are essential to shed light on the specific patient attributes and surgical variables responsible for the onset of preoperative anxiety.…”
Section: Risk Factors For Preoperative Anxietymentioning
confidence: 99%
“…The assessment of preoperative anxiety can be accomplished using either objective or subjective methods [32]. Objective approaches encompass both indirect and direct evaluations of anxiety levels, involving the estimation of sympathoadrenal system activation and the measurement of stress hormones, respectively [29,32]. Numerous studies have demonstrated that elevated preoperative anxiety levels are associated with increased heart rate, blood pressure, plasma cortisol, and catecholamine levels, alongside a reduction in heart rate variability and oxygen saturation [29,33].…”
Section: Measurement Of Preoperative Anxietymentioning
confidence: 99%